Բանկային գործունեության ռեսուրսատարողության արդյունավետության գնահատման մոտեցումները - Միքայել Սեդրակի Ջավադյան (ՀՀ ԳԱԱ հրատ.)
В условиях конкурентной деятельности коммерческие банки больше всего заинтересованы в улучшении финансовой устойчивости, путем расширения круга вовлеченных финансовых ресурсов. Однако нынешние условия финансового рынка требуют улучшения не только количественного, но и качественного состава финансовых ресурсов коммерческих банков. В статье предлагаются пути оценки эффективности управления финансовыми ресурсами с позиции улучшения конкурентности коммерческих банков. In a competitive environment, commercial banks are mostly interested in ensuring financial sustainability with respect to increasing the number of sources to attract financial resources. However, the current level of sophistication of the financial market requires not only improvement of quantitative, but also qualitative characteristics of the financial resources of commercial banks. The article proposes methods for estimating the efficacy of the financial resource management that rely on the prospects of improving the competitive position of commercial banks.
Keywords: Հասարակական գիտություններ; Տնտեսագիտության տեսություն; Ֆինանսներ